2009
DOI: 10.1155/2009/817205
|View full text |Cite
|
Sign up to set email alerts
|

Hydatid Cyst of the Rib: A New Case and Review of the Literature

Abstract: The hydatid cyst is not rare in our country, but bone lesions are less common. The disease often takes the appearance of abscess or malignant lesion. We report a case of a 35-year-old man with a hydatid cyst of the rib complicated with cutaneous fistula. The surgery allowed both diagnosis and treatment. Albendazole was then administered to prevent relapse.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
9
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 5 publications
0
9
0
Order By: Relevance
“…Involvement of ribs is very rare [2]. Hydatid cyst rib involvement shows infiltration to adjacent tissues by breaking down bone matrix as in our case [3]. Establishing the diagnosis of osseous hydatidosis first requires questioning of living conditions suspecting with radiological findings.…”
mentioning
confidence: 76%
See 2 more Smart Citations
“…Involvement of ribs is very rare [2]. Hydatid cyst rib involvement shows infiltration to adjacent tissues by breaking down bone matrix as in our case [3]. Establishing the diagnosis of osseous hydatidosis first requires questioning of living conditions suspecting with radiological findings.…”
mentioning
confidence: 76%
“…However, in our patient, Indirect hemagglutination test for Echinococcus was positive and high (positive test > 1/128). It has been reported that surgery and preoperative and postoperative albendazole therapy provide better outcomes [3]. Large doses over a long period of time would be a good clinical approach and may reduce the incidence of relapse.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…There have been reports of primary costal hydatididoreferred for surgical treatment. sis [9]. Although it has been hypothesized that the presence of lactic acid in the muscles does not allow the larvae to grow into cysts [10], sporadic cases of such primary involvement have been reported.…”
Section: Discussionmentioning
confidence: 99%
“…16 A number of reported patients demonstrated primary rib hydatidosis, which were most often treated by aggressive surgical resection. [17][18][19][20] Authors have reported that bone hydatid involvement of vertebrae, long bones, pelvis and skull usually result from vascular or lymphatic migration of viable parasites from other locations. 14 A systematic review from Tunisia, published in 2009, showed that the gold standard for an osseous cystic echinococcosis remains a wide surgical excision which can lead to excellent outcomes.…”
Section: Management Of Previously Published Hydatid Liver Cyst Rupturmentioning
confidence: 99%